Relationship between morpho-agronomic traits in tomato hybrids - Diel, Maria Inês; Zamban, Débora Turchetto; Olivoto, Tiago; krysczun, Dionatan Ketzer; Pinheiro, Marcos Vinícius Marques; Sari, Bruno Giacomini; Schmidt, Denise; Lúcio, Alessandro Dal'Col (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2019)
The objective of this study was to identify and estimate the relationships between production component variables and fruit yields in tomatoes. This experiment was conducted in a randomized block design with a 2×3×3 factorial arrangement, with two tomato hybrids (Netuno and San Vito), three doses of boron (H3BO3 - 0, 2, 4 g pit1)  and three calcium floral applications (no application; application every 7 days; and application every 14 days), totaling 18 treatments with four replications and 20 plants per plot. Pearson correlation coefficients were estimated between the measured variables and, after that, those with greater significance were selected for productivity with the Stepwise method and verification of multicollinearity using the number of condition and inflation factor of the variance. The correlations of the selected variables were decomposed into direct and indirect effects on fruit productivity with path analysis. There was a strong correlation between the variables, excluding the variables height, diameter and average mass of the fruits. Thus, there were cause and effect relationships between the independent variable total mass of the fruits and the principal variable total fruit yield. The variables diameter and total number of fruits did not contribute to an increased tomato production.